2020
DOI: 10.1021/acssuschemeng.0c00036
|View full text |Cite
|
Sign up to set email alerts
|

Waste PET Chemical Processing to Terephthalic Amides and Their Effect on Asphalt Performance

Abstract: A chemical recycling approach of mixed PET was demonstrated here that provides a mechanism by which PET waste can be efficiently recovered and repurposed to value-added products. The approach utilizes aminolysis of PET with a variety of amine nucleophiles, generating a small library of terephthalic amides with distinct structures, such as polar, nonpolar, and lipophilic. In order to probe the value of these products, the terephthalic amides were added to road-grade asphalt binder at 5 wt %, and the fresh resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Modified asphalt prepared using PET wastes has shown advantages with respect to rutting and fatigue parameters and creep deformation as well [ 51 , 52 ]. Merkel et al reported the use of chemically deconstructed mixed PET waste as an additive for asphalt [ 53 ]. The proposed approach utilizes the aminolysis process in which PET waste was treated with various amine nucleophiles to generate terephthalic amides with distinct structures such as polar, nonpolar, and lipophilic.…”
Section: Production Of Chemicals From Plastic Wastesmentioning
confidence: 99%
“…Modified asphalt prepared using PET wastes has shown advantages with respect to rutting and fatigue parameters and creep deformation as well [ 51 , 52 ]. Merkel et al reported the use of chemically deconstructed mixed PET waste as an additive for asphalt [ 53 ]. The proposed approach utilizes the aminolysis process in which PET waste was treated with various amine nucleophiles to generate terephthalic amides with distinct structures such as polar, nonpolar, and lipophilic.…”
Section: Production Of Chemicals From Plastic Wastesmentioning
confidence: 99%
“…There are several methods for recycling these waste plastics ( i.e. polyethylene terephthalate, PET) such as mechano-thermal processing, chemical recycling processes, 4 recycling using gas phase treatment, 5 enzymatic recycling, 6 and upcycling to higher value chemicals. 7 The employment of the recycling process for plastic recycling is based entirely on ease of processing and investment; therefore, recycling processes which are economically feasible, cost effective and environmentally friendly have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [83] successfully prepared toughened polylactic acid (PLA) nanocomposites with high stiffness and high rigidity by combination of 5% SNs modification and uniaxial pre-stretching. At present, polyester materials are widely used, and the requirements for polyester materials are not only to improve their own performance, but more importantly, to develop and apply new functions [84,85]. Luminescent polyester materials were considered to be one of the hotspots in functional polyester research [86].…”
Section: Introductionmentioning
confidence: 99%